Effect of Large Compress Aroma Lavender Therapy to Intensity Scale and Old Labor of I there are Active Phase Until Second Stage in Primigravida Mother in the Region Puskesmas Pagak District Malang - Widiastuti Widiastuti; Yuly Peristiowati; Siti Farida (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2018)
The pain of labor may potentially activate the sympathetic nervous system that inhibits endogenous oxytocin secretion, which can be resolved by the method of using warm compress therapeutic aromatherapy lavender to make vasodilatation of blood vessels so that the hormone oxytocin in the body more optimal and will help the contraction of the smooth muscle of the uterus that affect the labor so that run faster.Penelitian aims to determine the influence of warm compresses of lavender aromatherapy on pain intensity and duration of labor in active phase until premiere of second stage labor on primigavida maternity. The research design is True Experimental Design. Population of primigravida pregnant women who have interpretation of birth November-December 2017 in Pagak Puskesmas region consisting 42 respondents. The sampling technique using Simple Randomization was obtained 38 respondents (control and treatment group). Intensity was measured using VAS (Visual Analogue Scale) scale and the length of labor was measured by partograph (minutes) .The result of calculation of Hotelling T2 (sig 0,05) 62,8392.> 6,7216. H0 is rejected, meaning that there is a difference between the mean on the control and the average on the treatment. The use of warm compresses of lavender aromatherapy decreased the intensity of labor pain by 30.8%, while for the duration of labor acceleration occurred 26.4%. Thus warm compresses of lavender aromatherapy as one of the interventions in reducing the intensity of pain and labor acceleration in primigravid maternity, and can be applied to various health services.